Combatting Homelessness in Canada: Applying Lessons Learned from Six Tiny Villages to the Edmonton Bridge Healing Program - Wong, Anson; Chen, Jerry; Dicipulo, Renée; Weiss, Danielle; Sleet, David A.; Francescutti, Louis Hugo (International journal of environmental research and public health, 2020)
Emerging evidence shows that homelessness continues to be a chronic public health problem throughout Canada. The Bridge Healing Program has been proposed in Edmonton, Alberta, as a novel approach to combat homelessness by using hospital emergency departments (ED) as a gateway to temporary housing. Building on the ideas of Tiny Villages, the Bridge Healing Program provides residents with immediate temporary housing before transitioning them to permanent homes. This paper aims to understand effective strategies that underlie the Tiny Villages concept by analyzing six case studies and applying the lessons learned to improving the Bridge Healing Program. After looking at six Tiny Villages, we identified four common elements of many successful Tiny Villages. These include a strong community, public support, funding with few restrictions, and affordable housing options post-graduation. The Bridge Healing Program emphasizes such key elements by having a strong team, numerous services, and connections to permanent housing. Furthermore, the Bridge Healing Program is unique in its ability to reduce repeat ED visits, lengths of stay in the ED, and healthcare costs. Overall, the Bridge Healing Program exhibits many traits associated with successful Tiny Villages and has the potential to address a gap in our current healthcare system.